2023
DOI: 10.46303/repam.2023.11
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Decolonising of Medium of Instruction at South African Universities

Bonginkosi Hardy Mutongoza,
Chrispen Mutanho,
Manthekeleng Agnes Linake
et al.

Abstract: The 2015/6 #Rhodes Must Fall student protest reignited the debate to decolonise higher education in South Africa and many parts of the world. One way of achieving this is through decolonising the language of teaching and learning in higher education to increase access. Within this caveat, we anticipate that this article will add a crucial contribution to contemporary international and local debates on decolonising the medium of instruction by providing evidence from South African institutions’ unique challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 64 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…In most contexts, English ability, in general, was reported to be a significant factor affecting students' academic success (Devi, 2023;Millie, 2023;Soruç et al, 2022). Although the use of English as a medium of instruction has been growing as a global phenomenon in education (Macaro, 2020;Mutongoza et al, 2023;Tai and Wong, 2023), researchers have reported tension between policy and practice in its use, concerning the issue of language choice by teachers and students (Tai, 2023). This is because English is often used to teach academic subjects in contexts in which the first language of the majority of the population is not English.…”
Section: Language and Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…In most contexts, English ability, in general, was reported to be a significant factor affecting students' academic success (Devi, 2023;Millie, 2023;Soruç et al, 2022). Although the use of English as a medium of instruction has been growing as a global phenomenon in education (Macaro, 2020;Mutongoza et al, 2023;Tai and Wong, 2023), researchers have reported tension between policy and practice in its use, concerning the issue of language choice by teachers and students (Tai, 2023). This is because English is often used to teach academic subjects in contexts in which the first language of the majority of the population is not English.…”
Section: Language and Educationmentioning
confidence: 99%
“…In South Africa, one of the central themes in the quest to decolonise education has been the debates about the prioritisation of English as the medium of instruction in schools at the expense of Indigenous languages (Chimbunde and Kgari-Masondo, 2022;Mutongoza et al, 2023). Most learners in South Africa who have English as the LOLT are not native English speakers, and they come to learn through it while they are still learning the language (Mweli, 2018).…”
Section: Language and Educationmentioning
confidence: 99%
See 3 more Smart Citations